Development of material structure design method combining evolutionary algorithms and finite elements. Application for the optimisation of bio-inspired nano-composite fibres. - Σιμάτος, Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Ρευστών. Εργαστήριο Θερμικών Στροβιλομηχανών, 2014)
Inspired by the advanced mechanical properties of spider silk, the purpose of this diploma thesis is the optimisation of the structure of a novel, light weight, strong, bio-inspired material for automotive use. Certain spider dragline silks have an extraordinary combination of mechanical properties such as high strength, ductility and toughness, which outperform some of the best man-made materials in term of their mechanical properties. The structure of spider silk has been found to be a composite of two different phases, the stiff crystal and the amorphous phase which provides the extensibility of the fibre. The approach of this diploma thesis is to model the new materials using discrete building blocks that describe the different phases of the material. These building blocks co-operate in order to achieve a global result which surpasses the properties of each separate component. Using Evolutionary Algorithms as the optimisation method combined with an FEM tool as the evaluation method, the target is to demonstrate a design method where the internal layout of a material is automatically optimised for given target properties (high stiffness, high toughness, minimum material cost). Additionally, based on the optimisation findings, the direction for designing an ultimate virtual material may be defined, with ideal sub-component behaviour and interaction.